Hydrogen‐bond‐enabled dynamic kinetic resolution of axially chiral amides mediated by a chiral counterion - Fugard, A; Lahdenperä, A; Tan, J; Mekareeya, A; Paton, R; Smith, M (John Wiley and Sons, Ltd., 2019)
Non‐biaryl atropisomers are valuable in medicine, materials, and catalysis, but their enantioselective synthesis remains a challenge. Herein, a counterion‐mediated O‐alkylation method for the generation of atropisomeric amides with an er up to 99:1 is outlined. This dynamic kinetic resolution is enabled by the observation that the rate of racemization of atropisomeric naphthamides is significantly increased by the presence of an intramolecular O−H⋅⋅⋅NCO hydrogen bond. Upon O‐alkylation of the H‐bond donor, the barrier to rotation is significantly increased. Quantum calculations demonstrate that the intramolecular H‐bond reduces the rotational barrier about the aryl–amide bond, stabilizing the planar transition state for racemization by approximately 40 kJ mol−1, thereby facilitating the observed dynamic kinetic resolution.